Dynamics of technical efficiency and productivity change under central planning: The Romainian cement industry 1966 - 1989 - Mihai Cotfas; Almas Heshmati; Lennart Hjalmarsson (Stockholm School of Economics, The Economic Research Institute (EFI), 2000)
This paper investigates the time-path of efficiency and productivity change in the case of the Romanian cement industry 1966-1989. The analysis is based on different specifications of stochastic frontier models. The efficiency scores and the time paths of efficiency and technical change are found to vary substantially among models. The most important feature of the Romanian cement industry before the revolution in 1989 is a slow rate of productivity progress, and a corresponding catch up in the level of productive efficiency.
Keywords: C23; D24; L61; O30; 330; Productivity change; productive efficiency; stochastic frontiers; time-varying efficiency; panel data; cement industry; Romania; Zementindustrie; Technische Effizienz; Produktivität; Planwirtschaft; Rumänien